A survey study on relation of diabetes with people’s lifestyle in small cities of Bangladesh - Shahabuddin, Sabbir (Brac University, 2020)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Pharmacy, 2020.